Efeitos do metotrexate subaracnoideo sobre a medula espinal e as meninges de coelhos - Lemos, Marília Freitas de [UNESP] (2014)
Background: Cancer is a disease characterized by deviation of control mechanisms that regulate the survival, proliferation and differentiation of cells. Surgery, chemotherapy and radiotherapy are treatments used in oncology patients. Chemotherapeutic agents such as methotrexate (MTX) are considered effective antineoplastic agents. MTX belongs to the class of antimetabolites that act on the intermediary metabolism of cells on proliferation. For being increasingly used in cancer treatment protocols with progressively larger doses, the occurrence of central nervous tissue toxicity by MTX is increasing. The exact mechanism for triggering neurotoxicity has not been elucidated. The most common clinical manifestation of neurotoxicity after MTX administration is chemical aracnoiditis. Cases of cauda equina syndrome were also described. Objectives: To evaluate the effects of multiple subarachnoid doses of MTX over spinal cord and meninges of rabbits. Method: Thirty male young adults rabbits, breed genetic Group Botucatu, weighing between 3000 and 3900 g, with spinal length between 36 and 40 cm, and corporeal surface area between 0.22 and 0.19 m2 were divided by lot into three groups (G): G1, subarachnoid puncture; G2, saline solution; and G3, methotrexate. After intravenous anesthesia with xilaziana and ketamine, subarachnoid puncture was performed in S1-S2. Solution ion was performed inject in G2 and G3. G3 animals received MTX volume corresponding to 12 mg. m2 (0.1 mL); in G2, an equal volume of saline solution, was administered G1 only subarachnoid puncture was performed in S1- S2 intervertebral space. Solution injection was performed in G2 and G3. G3 animals received intrathecal MTX volume corresponded to 12mg.m2 (0.1 ml); in G2, an equal volume of saline solution was administered, while in G1 only subarachnoid puncture was performed. The same procedure was repeated four times at 7 days interval. Animals ...